A Physiotherapeutic Approach to Musicians' Health – Data From 614 Patients From a Physiotherapy Clinic for Musicians (INAP/O) - Zalpour, Christoff; Ballenberger, Nikolaus; Avermann, Florian (Frontiers in Psychology, 2021)
Currently, the treatment of musicians is an interprofessional approach. Playing-related health complaints may impact the performance of a musician. In Germany, a medical consulting hour for musicians exists, but those for athletes in sports medicine are not so common. The diagnosing and treatment procedure within the physiotherapy consultation for musicians follows a specific concept-b and requires knowledge of instruments and musician-specific complaints. Based on the consulting hour in a clinic in Osnabrueck, 614 case reports were part of this sample, of which 558 data sets were complete. The focus of the analysis is the instrument and the primary complaint. Also, the type of therapy is characterized, and the amount is calculated. Primary complaints of musicians, in general, are found most frequently in the spine and upper extremity. Musician complaints are different between instruments. Instrumentalists have a significantly higher chance to suffer from a primary complaint in the area of the upper extremity. Furthermore, the groups without an instrument (e.g., singing or dancing) are developing complaints in the anatomical area which they primarily use. Therefore, these types of therapy were used: physiotherapy, manual therapy, and osteopathy with an average of 5.9 treatment units. This study underpinned the importance of musician-specific physiotherapy as a profession to treat musicians. Also, an interdisciplinary approach is necessary to treat all aspects of complaints.